Cardiac functional consequences of stroke induced by transient middle cerebral artery occlusion in a rodent model. (25th November 2020) - Olah, A; Matyas, C; Barta, B.A; Sayour, A.A; Ruppert, M; Braun, S; Kovacs, A; Merkely, B; Nagy, Z; Radovits, T; Nardai, S
Abstract: Background: The cardiac functional consequences of ischaemic stroke are still need to be elucidated, while according to ethical issues only non-inasive measurents were carried out in patients underwent transient cerebral ischaemia. Purpose: We aimed at investigating left ventricular function using non-invasive and invasive modalities in a rat model of transient focal ischaemia. Methods: Age-matched, young adult rats were used for this study. Serial left ventricular echocardiographic measurements and speckle-tracking analysis were performed in rats (n=9) underwent transient middle cerebral artery occlusion (MCAO) before, during and immediately after the induction of stroke, with a follow-up at 24, 48, 72 hours; 7, 11 and 14 days. In another experimental setting, 48 hours after stroke induction (MCAO group, n=9) we characterized left ventricular function by pressure-volume analysis, that was compared to sham-operated controls (Co group, n=9). Results: Serial echocardiographic measurements showed impaired systolic function, that was most severe 48 hours after MCAO (global circumferential strain, GCS: −14.8±2.6% 48 hours after MCAO vs. −19.3±2.4% baseline, p<0.05). A complete recovery of systolic functional deterioration was observed after 14 days (GCS: −19.2±2.5% 14 days after MCAO vs. −19.3±2.4% baseline, n.s.). Heart weight (normalized to tibial weight) did not differ between MCAO and Co animals. Pressure-volume analysis revealed unaltered diastolic function and showed unchanged load-independent contractility index values (slope of end-systolic pressure-volume relationship, ESPVR: 2.56±0.29mmHg/μl MCAO vs. 2.55±0.59 mmHg/μl Co, n.s.) after MCAO. There was a tendency towards increased systolic pressure and deteriorated ventriculo-arterial coupling in animals underwent stroke. Conclusions: Our data suggests that MCAO is associated with reversible impairment of systolic function during echocardiographic measurements, however without alteration of intrinsic myocardial contractility. The tendency towards increased afterload might explain the observed alterations in rats underwent stroke. Funding Acknowledgement: Type of funding source: None